Early childhood education and care policy change: comparing goals, governance and ideas in Nordic contexts - Alexiadou Nafsika; Hjelmér Carina; Laiho Anne; Pihlaja Päivi (Routledge, 2022)
Early childhood education and care (ECEC) is changing across Europe, reflecting multiple-policy intentions and assumptions about education in early years, and the role of the state in supporting, funding and regulating its institutions. In this article, we examine the evolution of ECEC comparatively in Finland and Sweden, and we explore the shifts in goals, governance mechanisms and policy ideas that have characterised reforms in the sector. We draw on an analysis of policy documents, and argue that the incremental changes achieved over the last 50 years have been in response to changing goals assigned to ECEC and ideas about its roles and functions as part of the welfare and education sectors. The power of ideas in effecting policy change is tempered by established institutional framings, yet is visible in the early dominance of child-centred ideas, and the later controversies over the emergent labour-market and education-driven rationales of the post-2010s.